Efektivitas Konseling Kelompok Dengan Teknik Self Management Untuk Meningkatkan Kedisiplinan Belajar Siswa - Rositah Rositah; Raja Rahima (Fakultas Tarbiyah dan Keguruan, 2021)
The aim of this research was to find out the effectiveness of group counselling with self management techniques to increase students’ learning discipline. The research design was quasi experiment with non-equivalent control group design. This research was conducted to the students of SMPN 1 Keritang in academic years 2018/2019. The subjects of this research were 10 students who had low learning discipline. The sampling technique used in this research was purposive sampling technique. The techniques of collecting data were observation, closed questionnaire and documentation. In this case, the validity and reliability test used was SPSS for window release 23.0. The implementation of group counselling with self-management technique was based on the research indicators. The data analysis used to prove the hypothesis was Wilcoxon’s signed ranks test. The result of this research showed that the students’ learning discipline before they were treated on group counseling with self-management technique was categorized into low level with the average 41,3, and after the technique was applied, the students’ learning discipline increased into high categorization with the average 123,1. It can be said that there was a difference between pre-test and post-test scores. Therefore, it can be concluded that group counselling with self-management technique was effective to increase the students’ learning discipline that can be seen from the probability score Asymp. Sig (2-tailed) 0,005<0,05 with the result that Ha was accepted.